PRELIMINARY STUDY OF THE G6,ANTARCTIC ICE CORE - ショウジ, ヒトシ; フジイ, ヨシユキ; SHOJI, Hitoshi; FUJII, Yoshiyuki (National Institute of Polar Research, 1991)
P(論文) A 100m-long ice core was extracted at Site G6,Antarctica (73.1°S, 39.8°E) by members of JARE-27 in 1986. The excellent quality of the core obtained by electro-mechanical drill makes it possible to examine the environmental condition of snow deposition by conducting combined physical and chemical core analyses. Preliminary studies were carried out on visual stratigraphy, bulk density and electric DC conductivity on the core surface. The results obtained show that the average interval of ice layer/crust and DC conductivity cycle are 11 and 10cm of ice respectively. Bulk density data were treated so as to have the best-fit of the firnification equation (M. M. HERRON and C. C. LANGWAY, JR. : J. Glaciol., 25,373,1980) with data points under measured surface density of 0.38g/(cm)^3 and mean annual temperature of -40℃, which resulted in the accumulation rate of 10cm of ice/a. These values are significantly higher than the accumulation rate of 6 to 7cm of ice/a measured by stakes in the field (F. NISHIO et al. : JARE Data Rep., 137,49,1988). Further studies by chemical analysis and stable isotope measurement on the same core are going to be made for investigation of the core chronology which reflects the depositional feature of snow at the surface of the ice sheet. departmental bulletin paper